Using the smear method and Real-Time PCR technique in diagnosis of Toxoplasma gondii parasite in white male rats experimentally infected by parasite - Abbas Jasim, Ghaidaa; Naji Al-Khanaq, May (Al-Qadisiyah Journal of Pure Science, 2017)
The present study aims to isolate Toxoplasma gondii parasite and causing the experimentally infection and diagnosis of this infection by using the smear method and Real-Time PCR technique in different organs of white male rats such as brain, liver and testes . from aborted placentae of infected women and experimentally infection of male rats then diagnosed of this infection by impression smear that produced . The present study included 30 white male rats Rattus norvegicus aged ( 60-70) days averaged weight (200-250)gm . tissue cysts of parasite were presence in all prepared smears of brain ,liver and testes organs in different size and numerous numbers ,the percentage of infection by using Real-Time PCR was 26% in brain and 20% in liver and testes .this study was recorded the possibility of isolation of Toxoplasma gondii parasite and and diagnosis by using impression smears method and Real-Time PCR technique in different tissues of the organs of the experimental animals.